AB INITIO ELASTICITY AND THERMAL EQUATION OF STATE OF MGSIO3 PEROVSKITE - Oganov A.R.; Brodholt J.P.; Price G.D. (My University, 2001)
We have used high-temperature ab initio molecular dynamic simulations to study the equation of state of orthorhombic MgSiO3 perovskite under lower mantle pressure-temperature conditions. We have determined the Gruneisen parameter, γ, as a function of volume. Our state-of-the-art simulations, accurate to within 10%, resolve the long-standing controversy on thermal expansion (α) and Gruneisen parameter of MgSiO3 perovskite. Under ambient conditions we find the values for α and γ of 1.86x10-5 K-1 and 1.51, respectively, in excellent agreement with the latest experimental studies. Calculated elastic constants and the static equation of state at 0 K agree well with previous simulations. We have found no evidence for the high-temperature phase transitions of orthorhombic MgSiO3 perovskite to cubic or tetragonal phases at mantle temperatures.
Keywords: PEROVSKITE; LOWER MANTLE; EQUATIONS OF STATE; THERMAL EXPANSION; ELASTIC CONSTANTS; GRUNEISEN PARAMETERS; THERMOELASTIC PROPERTIES